2018
DOI: 10.2147/cmar.s174712
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of tumor vascular normalization: the key points from basic research to clinical application

Abstract: Tumor vascular normalization alleviates hypoxia in the tumor microenvironment, reduces the degree of malignancy, and increases the efficacy of traditional therapy. However, the time window for vascular normalization is narrow; therefore, how to determine the initial and final points of the time window accurately is a key factor in combination therapy. At present, the gold standard for detecting the normalization of tumor blood vessels is histological staining, including tumor perfusion, microvessel density (MV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 107 publications
(125 reference statements)
0
46
0
Order By: Relevance
“…Specifically, anti-angiogenic therapies could avert the nutrition of tumor cells by eradicating the existing tumor blood vessels and hinder the formation of new ones, thus suppressing intravasation in primary tumors and prevent the angiogenic switch in metastases [95]. Moreover, such therapies could normalize tumor blood vessels to alleviate the hypoxia levels within the tumor microenvironment and, therefore, reduce the malignancy degree and increase the efficiency of conventional therapies [96][97][98]. In this context, anti-angiogenic agents or angiogenic inhibitors have emerged as a relatively new class of drugs that aim to disrupt tumor vascularization [99].…”
Section: Conventional Anti-angiogenic Drugs and Their Limitationsmentioning
confidence: 99%
“…Specifically, anti-angiogenic therapies could avert the nutrition of tumor cells by eradicating the existing tumor blood vessels and hinder the formation of new ones, thus suppressing intravasation in primary tumors and prevent the angiogenic switch in metastases [95]. Moreover, such therapies could normalize tumor blood vessels to alleviate the hypoxia levels within the tumor microenvironment and, therefore, reduce the malignancy degree and increase the efficiency of conventional therapies [96][97][98]. In this context, anti-angiogenic agents or angiogenic inhibitors have emerged as a relatively new class of drugs that aim to disrupt tumor vascularization [99].…”
Section: Conventional Anti-angiogenic Drugs and Their Limitationsmentioning
confidence: 99%
“…Longitudinal monitoring of tumour vessel status, perfusion, and oxygenation will be required to accurately assess the clinical benefits in combination therapies. Circulating biomarkers, for instance, soluble VEGFR1, Ang2, collagen IV and apelin have been validated in some studies but so far no single predictive marker has been identified, even in the context of anti-VEGF therapy (11,62). Imaging modalities such as dynamic MRI, blood oxygenation level-dependent (BOLD) MRI or PET are useful technologies to indirectly monitor vascular function and oxygen status but difficult to implement into clinical routine (62).…”
Section: Clinical Challengesmentioning
confidence: 99%
“…Circulating biomarkers, for instance, soluble VEGFR1, Ang2, collagen IV and apelin have been validated in some studies but so far no single predictive marker has been identified, even in the context of anti-VEGF therapy (11,62). Imaging modalities such as dynamic MRI, blood oxygenation level-dependent (BOLD) MRI or PET are useful technologies to indirectly monitor vascular function and oxygen status but difficult to implement into clinical routine (62). Indeed, current insufficiencies in routine monitoring provide a strong incentive to develop alternative, more robust and durable normalisation strategies to increase the therapeutic window.…”
Section: Clinical Challengesmentioning
confidence: 99%
“…Currently, endostar is used clinically to treat advanced relapsed and metastatic cervical cancer.The platinumbased concurrent chemoradiotherapy maximizes the overall survival rate and bene ts patients with advanced cervical cancer, but the concurrent chemoradiotherapy still fails to effectively solve the problem of tumor proliferation and metastasis, with the overall survival rate hovering around 50% [7]. On July 20, 2017, endustar-recombinant human endostatin injection was successfully listed on the national medical insurance list, bene ting more patients.…”
Section: Current Situation and Problems Of Treatment Of Cervical Cancermentioning
confidence: 99%